Effects of a Combination of Resistance and Aerobic Exercise on Cardiorespiratory Fitness, Muscular Fitness, and Body Composition in a High-risk Patient with Inflammatory Cardiomyopathy, Potentially Malignant Arrhythmia, and Morbid Obesity - Nazir, Arnengsih; Miguna, Vindy Margaretha; Goesasi, Rachmat Zulkarnain; Tanuwidjaja, Deta (Faculty of Medicine, Universitas Airlangga, 2026)
Cardiomyopathy with concomitant heart failure and potentially malignant arrhythmia in patients with morbid obesity and mild restrictive lung disease causes significant functional impairment. Low-grade systemic inflammation accompanies the presence of these diseases. A 48-year-old woman undergoing phase II cardiac rehabilitation complained of easy fatigue. Cardiac rehabilitation consisting of moderate-intensity continuous training (MICT) 3 times 60 minutes with treadmill, arm, and leg ergometer, and resistance training was given. During MICT, the patient developed bigeminy without subjective complaint. After 6 weeks of exercise, an increase in VO2 max predicted by a 6-minute walking test (14.33 to 16.67), improvement in physical activity (low to moderate activity), and improvement in fatigue severity scale (43 to 27) were seen. Muscular fitness was also improved; muscle thickness showed an average increase of 0.25 centimeters with an increase in muscle strength. Body composition (2% decrease in body fat percentage and 4-level decrease in visceral fat) was also noted. Previous studies found that exercise increases VO2 max, improves endothelial function, and improves myocardial reserve flow. Muscle fiber adaptations also occur and include increased cross-sectional area of muscle, selective hypertrophy of fast-twitch fibers, decreased or maintained mitochondrial number and capillary density of muscle, and possible changes in energy sources. Combined exercise results in higher peak work capacity and VO2 peak than resistance or aerobic exercise alone. Although precautions must be taken due to the high risk of cardiovascular events as seen in this case, combined aerobic and resistance exercises can be prescribed to increase cardiorespiratory and muscular fitness and improve body composition.